Prevention of adolescent depression in the spanish-speaking world (2014)
ABSTRACT: This paper aims at presenting programs targeted at the prevention of adolescent depression applied with Spanish-speaking populations that have been developed in Spanish-speaking countries and are mostly published in Spanish. These programs have been developed under different cultural contexts in Spain and Latin-America. The main goal of this paper is to make the studies and movements of the Spanish-speaking literature in this field accessible to the non-Spanish-speaking part of the research community. Therefore, after an introduction referring to possible cultural differences regarding depression in general and epidemiological basics, several programs are introduced. In total 11 programs will be shortly presented and discussed. After revising the programs it can be concluded that in the Spanish-speaking world many programs have been developed and conducted following current state of the art-approaches for adolescent depression prevention. Further research is needed especially targeting possible cultural and contextual aspects of prevention measures and their efficacy and efficiency.